Esterase patterns in four Brazilian populations of Haematobia irritans - Castiglioni-Ruiz, L.; Bicudo, HEMD; Ceron, C. R. (Faculty Press, 1997)
Four population samples of Haematobia irritans (horn flies), collected from farms and subjected, or not, to insecticide control, were: analysed as to esterase bands by polyacrylamide gel electrophoresis. Eight esterase bands were detected in this species, a low number when compared with flies of other genera. The reduced number of esterase variants of H. irritans is attributed to their parasitic behaviour and blood-dependence for food. Unlike other fly species whose esterase bands exhibit affinity to both alpha- and beta-naphthyl acetates, the esterases in H. irritans seem to be of a single kind, all preferentially hydrolysing a-naphthyl. The four populations were very similar as to esterase bands. In relation to the frequencies of patterns resulting from combining bands, Nova Alianca and Birigui were more alike than the other two populations. Inhibitors were used in an attempt to classify five of the esterase bands. The results indicate one acetylcholinesterase, two acetylesterases and two carboxylesterases.
Keywords: Haematobia irritans; Esterases; gel electrophoresis